2015
DOI: 10.1039/c4ee02162b
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the composition of ultrathin, ternary alloy PtRuFe nanowires for the methanol oxidation reaction and formic acid oxidation reaction

Abstract: We have synthesized novel ultrathin ternary PtRuFe nanowires (NW) and probed both their methanol oxidation reaction (MOR) and formic acid oxidation reaction (FAOR) activities as a function of chemical composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
149
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(151 citation statements)
references
References 54 publications
2
149
0
Order By: Relevance
“…17 According to the cyclic voltammograms (CVs) shown in Figure 2a, the positions of the oxide reduction peaks of dendritic Pt-Ni-P and Pt-Ni alloy NPs have positive shifts relative to commercial Pt/C. This observation may be ascribed to the weakening interaction with the oxide species adsorbed on surface because of ligand effect caused by the doping of Ni and P. 13,18 Figure 2b and c exhibit the specific and mass activities of MOR recorded in 0.5 M H 2 SO 4 + 0.5 M CH 3 OH solution at 50 mV s -1 . For specific activities, the peak current density of MOR on dendritic Pt-Ni-P alloy NPs (0.65 mA cm -2 ) is 1.3 and 2.3 times than that of dendritic Pt-Ni alloy NPs (0.51 mA cm -2 ) and…”
mentioning
confidence: 87%
“…17 According to the cyclic voltammograms (CVs) shown in Figure 2a, the positions of the oxide reduction peaks of dendritic Pt-Ni-P and Pt-Ni alloy NPs have positive shifts relative to commercial Pt/C. This observation may be ascribed to the weakening interaction with the oxide species adsorbed on surface because of ligand effect caused by the doping of Ni and P. 13,18 Figure 2b and c exhibit the specific and mass activities of MOR recorded in 0.5 M H 2 SO 4 + 0.5 M CH 3 OH solution at 50 mV s -1 . For specific activities, the peak current density of MOR on dendritic Pt-Ni-P alloy NPs (0.65 mA cm -2 ) is 1.3 and 2.3 times than that of dendritic Pt-Ni alloy NPs (0.51 mA cm -2 ) and…”
mentioning
confidence: 87%
“…Zhang et al reported that PteCu alloy concave nanocubes with high-index facets exhibited substantially enhanced activity for MOR [14]. Wong et al prepared PtRuFe nanowires with higher MOR activity than Pt, Pt 7 Ru 3 , Pt 7 Fe 3 nanowires, and commercial Pt/C catalyst [15]. Adzic and co-workers synthesized monolayer-level Ru-and NbO 2 -supported Pt electrocatalysts with high Pt mass activity and improved durability for MOR through a galvanic replacement method [16].…”
Section: Introductionmentioning
confidence: 98%
“…Various strategies to directly mediate the deposition of catalyst particles have been reported, such as the urea-assisted electrochemical synthesis of flower-like Pt arrays [12], the ampholyte polystyrene spheres self-regulated deposition of noble metal nanoparticles [13], the silver-mediated shape control of Pt [14] and core-shell Ag@Pt nanoparticles [15], the glycinemediated syntheses of Pt-Cu nanocrystals [16] and Pt concave nanocubes with high-index {h k 0} facets [17] and Pt-Ni nanocrystals with high-index facets [18], the seed-mediated synthesis of monodispersed hyperbranched PtRu nanoparticles [19], and the soft template confined growth of ultrathin PtRuFe nanowires [20]. In these methods, at least one substance is introduced into the system as a surfactant, reducing agent, growth directing agent, etched species, seed, or template.…”
Section: Introductionmentioning
confidence: 99%